Diversidade da ictiofauna nas bacias do alto e médio Paranapanema - Ferreira, Natali Szeremeta (2022)
Freshwater fishes are fundamental components of biodiversity, and it is necessary to develop actions aimed at conserving these species in the face of anthropic changes in the XXI century. In this sense, it is fundamental to understand the mechanisms underlying the composition and distribution of these species along environmental gradients, applying different measures of diversity for this purpose. Alpha diversity represents the species richness in a given location, while beta diversity is a measure of species dissimilarity along environmental gradients, which includes two contrasting components of community structuring: species replacement and richness difference. Thus, alpha and beta diversities are part of regional species diversity, or gamma diversity. This study aimed to understand the taxonomic, functional, and phylogenetic diversity of the ichthyofauna of the Upper and Middle Paranapanema River. Presented as a book chapter, Chapter I includes a review of the ichthyofauna of rivers, streams, and reservoirs in the Upper and Middle Paranapanema River. In this sense, 128 species were recorded in these environments, with greater representation from the Characidae and Loricariidae families. The highest species richness and the lowest proportion of autochthonous species from the Upper Paraná River (83%) were found in reservoirs, with 20 species recorded only in these environments. The headwater streams have the lowest richness and the highest proportion of autochthonous species, being essential for the conservation of endemic species and species that are exclusive to this type of environment. Then, Chapter II investigates different measures of diversity for two spatial scales in the Paranapanema River: the Alto Paranapanema basin and the Pinhal sub-basin, for taxonomic, functional and phylogenetic diversity. The values of total alpha and beta diversity, as well as the values of the substitution and richness difference components of beta diversity were estimated. Next, the relationship of taxonomic beta diversity to the environment was analyzed, and the contribution of local, spatial, and stream-surrounding effects to the dissimilarity were divided. The gamma diversity and the taxonomic, functional and phylogenetic alpha and beta diversities were higher for the Alto Paranapanema basin compared to the Pinhal sub-basin. Furthermore, the replacement component was greater than the richness difference for the taxonomic beta diversity in the two spatial scales. The effect of the surrounding area was the most significant finding to explain the compositional dissimilarity for the basin, while the geographic distance was the most important result to explain the total beta diversity for the sub-basin. The general findings show the importance of using different scales in the study of stream fish diversity, as well as the relevance of headwater streams in order to preserve the diversity of ichthyofauna at a river basin scale.